ANALISIS KEMEMPUAN SISWA SMP/MTS KOTA BENGKULU DALAM MENYELESAIKAN SOAL MATEMATIKA TIMSS - Edi Susanto; Agus Susanta; syafdi maizora; Rusdi Rusdi (Jurnal THEOREMS (The Original Research of Mathematics), 2021)
The purpose of this study was to describe the ability of junior high school students in Bengkulu City in solving math problems based on Trend International Mathematics and Science (TIMSS).  This research was a survey research with a qualitative descriptive approach. The population in this study were all students of Class IX from 40 schools public and private junior high school in Bengkulu City. The sample selection was carried out in two stages, namely stratified random sampling to select schools and simple random sampling to select classes. The sample consisted of 12 Junior high schools in Bengkulu City. Data collection was done by distributing test instruments. The research instrument was 20 items that consist of 15 multiple choices and 5 short answers that were reviewed from the TIMSS problems in 2011 and 2015. Data analysis was done by using descriptive statistics. The results showed that the ability of junior high school students in Bengkulu City in terms of content aspects, namely: (1) geometry  of 23.46% (low), (2) data and chance of 50.40% (low), (3) algebra and number of 59.18% (enough).